Success Factors for the Development of Micro, Small, and Medium Industrial Clusters in Indonesia (Journal of Asian Development Studies, 2023)
Since the 1970s, the Indonesian government has seriously focused on developing MSMEs with various programs and facilitation, including facilitating existing MSME industrial clusters. The main objective of this article is to examine the development of MSME industrial clusters in Indonesia using the latest available data. This study focuses on analyzing the development of the MSME industrial cluster in Indonesia, the main problems, and determining factors for the success of developing an MSME industrial cluster in Indonesia. The study analyzes secondary data from Indonesia's National Agency of Statistics and reviews critical literature on developing MSME industrial clusters in Indonesia. The findings of this study show that the number of MSME industrial clusters is concentrated on the island of Java, where more than 50% of the population is located, and is the most advanced region in economic development and industrialization in Indonesia. According to industry groups, the most numerous MSME clusters are in the food and woodworking industries. Second, many MSME clusters still need to receive guidance from the government. In many cases, government policies supporting the development of cluster MSMEs through a clustering approach have been unsuccessful. Third, most of the MSME industrial cluster comes from "artisanal" circles dominated by micro-enterprises (MIEs).